Approach to a conceptualization of fundamental rights - Delgado Motoa, Beatriz (DIXI, 2019)
Objective: the essay is aimed at clearly establishing the concept of fundamental rights, based on the different philosophical currents that guide the subject, as well as being able to determine it in the countries that make up Unasur. Methodology: the article study what are the different existing notions about these, which are considered as fundamental. Results: the world, and especially this region, has made great progress in the protection of fundamental rights. Conclusions: the approximation of a common concept to all these countries is presented, in order to achieve its protection in a uniform way.